2004
DOI: 10.1172/jci200419540
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 induces bone marrow reticulin fibrosis in hairy cell leukemia

Abstract: Nonstandard abbreviations used: B cell chronic lymphocytic leukemia (B-CLL); bone marrow (BM); BM fibroblast (BMF); BM mononuclear cell (BMMC); BM plasma (BMP); BM stromal cell (BMSC); hairy cell (HC); HC leukemia (HCL); healthy donor (HD); peripheral blood plasma (PBP); procollagen type III aminoterminal propeptide (PIIINP). Conflict of interest:The authors have declared that no conflict of interest exists. IntroductionHairy cell leukemia (HCL) is a chronic lymphoproliferative disorder characterized by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…These authors suggest that TINP1, together with two other noncharacterized genes found in this region, constitute a candidate tumor suppressor gene (21). Moreover, recent evidence suggests that high levels of transforming growth factor-␤ are secreted by hairy cells and favor the progression of the pathology (22). An appealing hypothesis would therefore be that deregulation of TINP1 expression could participate in the progression of the disease either because of chromosomal abnormalities or because of stimulation by transforming growth factor-␤.…”
Section: Discussionmentioning
confidence: 99%
“…These authors suggest that TINP1, together with two other noncharacterized genes found in this region, constitute a candidate tumor suppressor gene (21). Moreover, recent evidence suggests that high levels of transforming growth factor-␤ are secreted by hairy cells and favor the progression of the pathology (22). An appealing hypothesis would therefore be that deregulation of TINP1 expression could participate in the progression of the disease either because of chromosomal abnormalities or because of stimulation by transforming growth factor-␤.…”
Section: Discussionmentioning
confidence: 99%
“…These include TGF-b, fibroblast growth factor 2 (FGF-2), and platelet-derived growth factor. [109][110][111][112] Some of the most compelling evidence for a prominent role of TGF-b in myelofibrosis comes from a study using Tgfb1-null mice. To induce myelofibrosis, irradiated mice were transplanted with BM cells transduced with vectors containing the thrombopoietin gene.…”
Section: The Diseased Bm Microenvironmentmentioning
confidence: 99%
“…These include TGF-b, mainly TGF-b1, basic fibroblast growth factor and platelet-derived growth factor. [105][106][107][108] Some of the strongest evidence for a prominent role of TGF-b in the generation of myelofibrosis involved the use of BM cells from Tgf-b1 null mice. To induce myelofibrosis, irradiated mice were transplanted with BM cells transduced with vectors containing the thrombopoietin gene.…”
Section: Spotlightmentioning
confidence: 99%